Quando a IA imagina a Amazônia - René Somain (Confins)
To experiment with artificial intelligence software generating images from text (prompts), a test was carried out with the expressions "Amazon of rivers", "Amazon of highways" and "Amazon of cities". Secondly, the possibility of illustrating Thiago Oliveira Neto's thesis "O transporte rodoviário de passageiros na Amazônia brasileira" was tested. Copilot, CrAIyon, Dreamstudio, Firefly, Ideogram and Adobe Illustrator were used for this test.